Changes in renal function increase the need for advanced ventilatory support and increase the risk of mortality in critically ill patients with COVID‑19. Issue 3 (2022) - MORAIS, NICKSON MELO DE; LEONE, LARA CANDICE COSTA DE MORAIS; ALMEIDA, VALÉRIA DUARTE DE
No abstract available